Activation of human polymorphonuclear neutrophils by streptolysin O from Streptococcus pyogenes leads to the release of proinflammatory mediators - Nilsson, Maria; Sørensen, Ole E.; Mörgelin, Matthias; Weineisen, Maria; Sjöbring, Ulf; Herwald, Heiko (Thrombosis and Haemostasis, 2006)
Streptococcus pyogenes is an important Gram-positive pathogen that is strictly limited to infections in humans. Here we report that streptolysin O (SLO),a cytolytic exotoxin secreted by S. pyogenes, activates human polymorphonuclear neutrophils (PMNs) by perforating these cells. This appears to be followed by an influx of Ca2+ and p38 MAPK activation. As a consequence, PMNs secrete heparin-binding protein, a potent inducer of vascular leakage, and neutrophil-borne proteins, including LL-37, α-defensins, and elastase. The results of the present work therefore suggest that the interaction between SLO and PMNs evokes an exaggerated host response which may contribute to the pathogenesis of local and generalized S. pyogenes infections.
Keywords: Infectious diseases; polymorphonuclear neutrophils; Streptococcus pyogenes; streptolysin O; degranulation